BENTUK SINGKAT DALAM TUTURAN BAHASA JAWA DI SURAKARTA - Basuki Basuki (CARAKA, 2015)
This research is a descriptive qualitative research which focuses on the form, function, and changing meaning of the shortened form of Javanese language, mainly in Surakarta area. The result of the research shows that (1) there are three forms of shortened use of language in the Javanese speech community; (a) shortened form of as the result of sound elimination in the beginning of the word, (b) shortened form of as the result of sound elimination of the middle of syllables, (c) shortened form of as the result of sound elimination at the end of the word. (2) There are three function of shortened use of language in the Javanese speech community; (a) interpersonal function, (b) directive function, and (c) personal function. (3) The changing meaning in the use of shortened form of Javanese language are (a) the changing of polite meaning into rude meaning, (b) the changing of rude meaning into a polite one.